Research on the construction method of high-speed railway tunnel in sandy loess and fine sand composite strata - Dianhong Xu; Bingzhou Yan; Honglu Qu; Baona Ma; Jinghe Wang; Xu Wang (Scientific Reports)
Abstract The Panxian Mountain Tunnel of the Zhongwei to Lanzhou Railway was selected as the engineering project for this study. Physical and mechanical parameters of sandy loess and fine sand were obtained through indoor experiments. Numerical simulation methods were employed to compare and analyze the surrounding rock’s deformation and the stress characteristics of initial support under the combination of three step temporary arch method and different advanced support. Considering deformation control effect and technical difficulty, this paper proposed a tunnel construction method of “three-step temporary ininverted arch + temporary vertical support + advanced horizontal jet grouting piles” (Abbreviated as TTA) in sandy loess and fine sand composite strata. On site monitoring results revealed that the surrounding rock pressure is between 60 and 150 kPa, below the theoretical loosening pressure. The initial support exhibiting characteristics of small eccentric compression, and the safety factor was below the allowable value according to the standards. Numerical simulation and on-site monitoring have mutually verified the effectiveness of the proposed construction method. The research results hold significant reference value for selecting construction methods for large-section tunnels in similar stratum conditions.